English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

a(3tx-2b)=c(dx-2)?

2007-08-23 09:48:23 · 4 answers · asked by [xo♥ox] 1 in Science & Mathematics Mathematics

4 answers

This is a literal equation, just treat the letters as you would numbers:

distribute:

3atx - 2ab = cdx - 2c

bring terms with x to left side, others to the right:

3atx - cdx = 2ab - 2c

factor out the x:

x (3at - cd) = 2ab - 2c

divide by what multiplies x:

x = (2ab - c) / (3at - cd)

That's it!

2007-08-23 09:56:22 · answer #1 · answered by Marley K 7 · 1 0

I forgot.. I think

a(3tx-2b)=c(dx-2)
a3tx-2b=cdx-2
a3tx-cdx=2b-2
x(a3t-cd)=2b-2
x=2b-2/a3t-cd

2007-08-23 16:59:13 · answer #2 · answered by Anonymous · 0 0

3atx - 2ab = cdx - 2c
(3at - cd) x = 2ab - 2c
x = 2(ab - c) / (3at - cd)

2007-08-27 14:21:19 · answer #3 · answered by Como 7 · 0 0

3atx - 2ab = cdx -2c

3atx - cdx = 2ab - 2c

x (3at - cd) = 2ab - 2c
or x (3at - cd) = 2 (ab-c)

x = (2ab - 2c) / (3at - cd)
or x = 2 (ab-c) / (3at - cd)

2007-08-23 16:57:36 · answer #4 · answered by Alison 2 · 0 0

fedest.com, questions and answers